MARDS Workshop Proceedings - Debevc, Matjaž; Lovrenčič Držanič, Irena (2020)
The collection contains contributions by authors who were presented at a workshop within the Erasmus + project MARDS in Maribor, at the University of Maribor.
Keywords: Doctoral study; higher education; e-learning; distance learning; MARDS; study evaluation